2009
DOI: 10.1073/pnas.0810793106
|View full text |Cite
|
Sign up to set email alerts
|

Growth retardation and altered autonomic control in mice lacking brain serotonin

Abstract: Serotonin synthesis in mammals is initiated by 2 distinct tryptophan hydroxylases (TPH), TPH1 and TPH2. By genetically ablating TPH2, we created mice (Tph2 ؊/؊ ) that lack serotonin in the central nervous system. Surprisingly, these mice can be born and survive until adulthood. However, depletion of serotonin signaling in the brain leads to growth retardation and 50% lethality in the first 4 weeks of postnatal life. Telemetric monitoring revealed more extended daytime sleep, suppressed respiration, altered bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
328
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(359 citation statements)
references
References 41 publications
30
328
0
1
Order By: Relevance
“…Following Tph2 inactivation, growth retardation but normalization after weaning (with normal weight four months of age) was also observed by Alenina et al [21]. In contrast, it was reported that Tph2 2/2 mice display a reduced fat pad and size and that, at one and a half and three months, they display both reduced food intake and increased metabolism linked to altered leptin regulation [131].…”
Section: (C) Monoamine Transmitters and Neuronsmentioning
confidence: 82%
See 1 more Smart Citation
“…Following Tph2 inactivation, growth retardation but normalization after weaning (with normal weight four months of age) was also observed by Alenina et al [21]. In contrast, it was reported that Tph2 2/2 mice display a reduced fat pad and size and that, at one and a half and three months, they display both reduced food intake and increased metabolism linked to altered leptin regulation [131].…”
Section: (C) Monoamine Transmitters and Neuronsmentioning
confidence: 82%
“…Elimination of 5-HT synthesis does not appear to affect GABA concentrations in whole-brain tissue [21], but measurement in different brain regions of Tph2 KO mice in combination with unbiased stereological assessment of GABAergic cell subpopulations in the hippocampus and amygdala revealed differential alterations [102]. While hippocampal GABA concentrations were increased in Tph2 2/2 mice, GABA was increased in heterozygous Tph2 þ/2 mice in the amygdala compared with Tph2 2/2 and wild-type control mice but opposite in prefrontal cortex.…”
Section: (C) Monoamine Transmitters and Neuronsmentioning
confidence: 99%
“…There are two isoforms of the enzyme; Tph1 which is predominantly expressed in the periphery, whereas Tph2 is predominantly expressed in the brain [38]. A Tph2 knockout in mice leads to retarded growth and lower body weight in early postnatal development [39,40]. An independent study found decreased food intake and bone mass in these mice [41] and the effects on body weight could possibly be gender dependent [42].…”
Section: Brain 5-ht and Satietymentioning
confidence: 99%
“…The generation of Tph2 -/-and SERT -/-mice has been described in detail elsewhere [15,20]. Both Tph2 -/-and SERT -/-mice have been established on a pure C57BL/6 genetic background [21].…”
Section: Animalsmentioning
confidence: 99%